The Human Leukocyte Antigen G as an Immune Escape Mechanism and Novel Therapeutic Target in Urological Tumors - Jasinski-Bergner, Simon; Eckstein, Markus; Taubert, Helge; Wach, Sven; Fiebig, Christian; Strick, Reiner; Hartmann, Arndt; Seliger, Barbara (Frontiers in Immunology, 2022)
The non-classical human leukocyte antigen G (HLA-G) is a potent regulatory protein involved in the induction of immunological tolerance. This is based on the binding of membrane-bound as well as soluble HLA-G to inhibitory receptors expressed on various immune effector cells, in particular NK cells and T cells, leading to their attenuated functions. Despite its restricted expression on immune-privileged tissues under physiological conditions, HLA-G expression has been frequently detected in solid and hematopoietic malignancies including urological cancers, such as renal cell and urothelial bladder carcinoma and has been associated with progression of urological cancers and poor outcome of patients: HLA-G expression protects tumor cells from anti-tumor immunity upon interaction with its inhibitory receptors by modulating both the phenotype and function of immune cells leading to immune evasion. This review will discuss the expression, regulation, functional and clinical relevance of HLA-G expression in urological tumors as well as its use as a putative biomarker and/or potential therapeutic target for the treatment of renal cell carcinoma as well as urothelial bladder cancer.